Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V.; Münkhoff, Eva; Scheer, L. K. (ISBM 2014 Academic Conference, San Francisco, CA)

Salespersons’ solution crafting capability: A knowledge-based perspective - Münkhoff, Eva; Eggert, A.; Terho, H.; Haas, A.; Ulaga, W. (ISBM 2014 Academic Conference, San Francisco, CA)

Selling value in business markets: Why a powerful idea often fails - Eggert, A.; Haas, A.; Terho, H.; Ulaga, W.; Münkhoff, Eva (ISBM 2014 Academic Conference, San Francisco, CA)

Revenue and Profit Implications of Industrial Service Strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Münkhoff, Eva (Journal of Service Research)
In many business markets, manufacturers seek service-led growth to secure their existing positions and continue to grow in increasingly competitive environments. Using longitudinal data from 513 German mechanical engineering companies and latent growth curve modeling, this study offers a fine-grained view of the financial performance implications of industrial service strategies. By disentangling the revenue and profit implications of industrial service strategies, findings reveal that such strategies increase both the level and the growth of manufacturing firms’ revenue streams. In contrast, they reduce the level but improve the growth of manufacturers’ profits. Results further suggest that services supporting the clients’ actions (SSC) and services supporting the supplier’s product (SSP) affect performance outcomes in different ways. SSCs directly affect revenue and profit streams. In turn, SSPs display only indirect effects on financial performance mediated through SSCs. A moderator analysis identifies two organizational contingencies that facilitate service business success: Only companies with decentralized decision-making processes and a high share of loyal customers can expect favorable financial results from industrial service strategies. In summary, this research provides significant insights and managerial guidance for turning service strategies into financial successes.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Embracing complex causality with the QCA method: An invitation - Schneider, Martin; Eggert, Andreas (Journal of Business Market Management)

Are we on track with sustainability literacy? - Hahn, Rüdiger; Reimsbach, Daniel (Journal of Global Responsibility)
Purpose – In this viewpoint, the authors aim to discuss sustainability issues in university education. Balancing what we call the “Accounting View” and the “Sustainability View”, the authors illuminate the status of value relevance of sustainability information and question the depth of business students' processing of this information. Design/methodology/approach – The discussion was triggered by an experimental study on sustainability disclosure which revealed interesting findings related to the participating students' prior sustainability and accounting coursework. The authors start the viewpoint from these findings and contrast them with existing views on sustainability and accounting (education). Findings – The amount of accounting coursework was positively related to the probability of including sustainability information in future stock value estimates, whereas this applied only marginally to sustainability coursework. However, students with more sophisticated sustainability knowledge seemed to scrutinize the given sustainability information more deeply, while students with “pure” accounting knowledge seemed more willing to simply accept the information. Practical implications – The authors argue for advancements in the curriculum for business students that foster critical thinking and might prevent students (and thus potential future managers) from using sustainability information superficially. The authors caution against regarding sustainability issues as an “add-on” to existing courses and curricula and call for a combination of integrating sustainability issues in (core) business courses and offering standalone courses on sustainability management or CSR. Originality/value – Triggered by findings from an experimental study, the authors contrast different opinions on sustainability education of business students and offer a new viewpoint on the (supposed) value relevance of sustainability information for future business leaders.
Keywords: Business and International Management

Modeling sequential R&D investments: a binomial compound option approach - Hauschild, Bastian; Reimsbach, Daniel (Business Research)
Abstract In this paper, we propose a binomial approach to modeling sequential R&D investments. More specifically, we present a compound real options approach, simplifying the existing valuation methodology. Based upon the same set of assumptions as prior models, we show that the number of computational steps for valuing any compound option can be reduced to a single step. We demonstrate the applicability of our approach using the real-world example of valuing a new drug application. Overall, our work provides a heuristic framework for fostering the adoption of binomial compound option valuation techniques in R&D management.
Keywords: Business; Management and Accounting (miscellaneous)

Eine Systematisierung komplementärer Zugänge zur Lehrentwicklung am Beispiel des Förderprogramms Lehren - Jenert, Tobias
Das Förderprogramm Lehren, organisiert von der Alfred Toepfer Stiftung F.V.S., kombiniert und erprobt verschiedene Ansätze zur Entwicklung der Lehrqualität an Hochschulen. Der vorgeschlagene Beitrag charakterisiert die unterschiedlichen Zugänge, beschreibt der Potenziale und Grenzen und reflektiert Möglichkeiten, komplementäre Lehrentwicklungs-Ansätze zu kombinieren. Das "Lehren Jahresprogramm" bringt Lehrende, Hochschuldidaktiker/-innen und Leitungspersonen im Rahmen von fünf themenbezogenen Workshops zusammen. Der Austausch im Rahmen der Workshops soll die Teilnehmenden neben der individuellen Kompetenzentwicklung und gegenseitiger Perspektivübernahme dabei unterstützen, Innovationsprojekte an ihren Hochschulen zu entwickeln bzw. zu implementieren. Das Jahresprogramm vertritt damit einen Ansatz, der Lehrqualität durch die Gestaltung organisationaler Rahmenbedingungen an den Hochschulen zu entwickeln versucht. Mit der Kombination verschiedener Akteursgruppen sowie durch die zentrale Organisation des Programms soll eine Community von Lehrentwickler/-innen geschaffen werden, die Strategien zur lehrbezogenen Organisationsentwicklung an Hochschulen entwickelt und teilt. Demgegenüber setzt das "Lehren-Kolleg" auf einen fachdidaktischen Zugang zur Lehrentwicklung an Hochschulen. So befassen sich im aktuellen Durchgang Teams aus sieben Hochschulen mit der Gestaltung der Mathematikausbildung in den Ingenieurswissenschaften. Auch hier werden von den teilnehmenden Hochschulvertreter/-innen jeweils Innovationsprojekte bearbeitet, wobei diese stets auf die fachdidaktische Fragestellung des Kollegs ausgerichtet sind. In diesem Ansatz spiegelt sich die starke Bedeutung wissenschaftlicher Disziplinen an Hochschulen wider. Die disziplinäre Zugehörigkeit gilt als stärkstes Element der beruflichen Identität von Hochschullehrenden und schlägt sich dementsprechend in den Kulturen einzelner Studienfächer nieder. Der Beitrag stellt die beiden Zugänge zur Lehrentwicklung - organisations- und fachbezogen - vor dem Hintergrund erster Ergebnisse einer umfangreichen Begleitforschung dar. Dabei geht es nicht darum, die Ansätze konkurrierend darzustellen und sie hinsichtlich ihrer Effektivität zu vergleichen (i.S. der Debatte Fach- versus allgemeine Didaktik). Vielmehr werden die komplementären Potenziale und Schwächen herausgearbeitet, um schliesslich das Konzept eines kombinierten Ansatzes der Lehrentwicklung zu entwerfen, der eine möglichst umfangreiche Dissemination im Rahmen der komplexen Organisationsstrukturen von Hochschulen ermöglichen kann.
Keywords: Lehrentwicklung; educational development

A matter of degree: the continuing training gap for women in Europe - Wozny, Caroline; Schneider, Martin (Socio-Economic Review)

Zielorientiertes Management von Logistikdienstleistungen in Netzwerken kooperierender Unternehmen - Puls, Christoph

Integrierte Lagerstandort- und -kapazitätsplanung als Gegenstand der strategischen Logistk - Ortgiese, Malte

Loyalitätswirkung des geschenkten bevorzugten Kundenstatus – Eine theoretische und empirisch-experimentelle Analyse - Steinhoff, Lena

How Profound Is the Allure of Endowed Status in Hierarchical Loyalty Programs? - Eggert, A.; Garnefeld, I.; Steinhoff, Lena (Customer & Service Systems, Special Issue: Customer Empowerment, 1 (1))

Three Perspectives for Making Loyalty Programs More Effective - Steinhoff, Lena; Palmatier, R. W. (Customer & Service Systems, Special Issue: Customer Empowerment, 1 (1))

Consequences of Customer Engagement: How Customer Engagement Alters the Effects of Habit-, Dependence-, and Relationship-Based Intrinsic Loyalty, Marketing Science Institute (MSI) Working Paper Series. - Henderson, C. M.; Steinhoff, Lena; Palmatier, R. W.

Zur Attraktivität von Advance Tax Rulings (ATRs) und Advance Pricing Agreements (APAs) für Investoren und Steuerbehörden: The Attractiveness of Advance Tax Rulings (ATRs) and Advance Pricing Agreements(APAs) for Investors and Tax Authorities, Synopse zur Dissertation - Kortebusch, Pia

AGnovel and other Graphic novels like Twilight - Schneider, Jennifer

Wissenschafts-Praxis-Kooperation in designbasierter Forschung: Im Spannungsfeld zwischen wissenschaftlicher Gültigkeit und praktischer Relevanz - Brahm, Taiga; Jenert, Tobias (Zeitschrift für Berufs-und Wirtschaftspädagogik-Beihefte (ZBW-B))
Designbasierte Forschung zielt darauf, praktische Problemstellungen zu lösen und gleichzeitig wissenschaftliche Theorien (weiter) zu entwickeln. Dabei durchläuft designbasierte Forschung in der Regel die Phasen der Problemdefinition, der Entwicklung eines didaktischen Designs, der zyklischen Design-Implementation sowie der Evaluation und Reflexion in enger Kooperation von Wissenschaft und Praxis. Inwieweit es mittels designbasierter Forschung gelingen kann, wissenschaftliche Gültigkeit und praktische Relevanz von Forschung gleichermassen zu steigern, wird im Beitrag anhand des Konzepts multipler Signifikanzen erörtert. Dabei wird diskutiert, wie die Gestaltung der Kooperation von Forschenden und Praktikern/-innen dazu beitragen kann, die praktische, statistische, klinische und wirtschaftliche Signifikanz des designbasierten Forschungsprozesses sicherzustellen.
Keywords: Design-based research; design research; validity; significance; Bildungsforschung; designbasierte Forschung; Wissenschafts-Praxis-Kommunikation

Nicht für alle gleich: subjektive Wahrnehmungen des Übergangs Schule-Hochschule - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Zeitschrift für Hochschulentwicklung)
Beim Übergang von der Schule in die Hochschule stehen Studienanfänger/innen einer Vielzahl von Herausforderungen gegenüber (z. B. Ankommen am Studienort, Bewältigung der Studienanforderungen). Dabei gibt es - abgesehen von deskriptiven Untersuchungen - kaum gesicherte Forschungsergebnisse darüber, in welchem Umfang individuell unterschiedliche Eingangsvoraussetzungen die wahrgenommene Intensität der Übergangsherausforderungen beeinflussen. Mittels einer Längsschnittstudie wird eine Kohorte von Studienanfängerinnen und -anfängern anhand ihrer Selbstwirksamkeit in Gruppen eingeteilt. Es wird gezeigt, dass diese Gruppen sich auch im Ausmass der erwarteten und erlebten Herausforderungen des ersten Studienjahres signifikant unterscheiden.
Keywords: Studienanfänger/innen; Herausforderungen; Übergang; Selbstwirksamkeit; Angst

Die Verjährung des Anspruchs auf Rückerstattung des Bearbeitungsentgelts - Bartlitz, David (Zeitschrift für Bankrecht und Bankwirtschaft (ZBB))